Odpowiedzi

Najlepsza Odpowiedź!
2010-01-18T22:01:10+01:00
A)
2x(x - 5) - 3(x² - 2x)x =
2x²-10x-3x³+6x²=
-3x³+8x²-10x

b)
a(a + b + c) - b(a - b + c) - c(a - b -c) =
a²+ab+ac-ab+b²-bc-ac+bc+c²=
a²+b²+c²

c)
x(x² + 2x +1) - (-4x³ + 8x² -6)/2=
x³+2x²+x+2x³-4x²+3=
3x³-2x²+x+3
3 5 3
2010-01-18T22:05:55+01:00
A) 2x kwadrat - 10x - 3x sześcian - 6x kwadrat =
-3x sześcian - 4x kwadrat - 10x

b) a kwadrat + ba +ca - ba + b kwadrat - cb - ca + cb + c kwadrat =
a kwadrat + b kwadrat +c kwadrat

c) 3x sześcian - 2x kwadrat +x +3
3 5 3
2010-01-18T22:07:18+01:00
A) 2x(x-5) - 3(x² - 2x)x = 2x²-10x-3x²+6x*x=2x²-10x-3x²+6x²=5x²-10x
b)a(a+b+c)-b(a-b+c)-c(a-b-c)=a²+ab+ac-ab+b²-bc-ac+bc+c²=a²+b²+c²
c)x(x²+2x+1)-(-4x³+8x²-6):2=x³+2x²+x-(-2x³+4x²-3)=x³+2x²+x+2x³-4x²+3=3x³-2x²+x+3
2 5 2